Paget's disease of bone in ethnic Thai presented with urologic symptoms and misleading as metastatic prostate cancer: Report of a case with a review of the literature - Supanat Sirikulchayanonta (2018)
Paget's disease of bone is common in some parts of Europe and in countries inhabited by European emigrants. In Western Countries, Paget's bone disease is one of the priorities in differential diagnosis for elderly patients who present osteoblastic lesions, so it is unlikely to be overlooked, even though patients may present symptoms unrelated to bone lesions. However, in Asian countries where Paget's disease is rare, metastatic prostate cancer appears to be the most common cause for osteoblastic lesions, thus, the Paget's disease is unlikely to be of much concern. This may lead to undue emphasis on investigations to support the diagnosis of prostate cancer. In this report, a 69 year-old man presented pain in the right leg and difficulty urinating. The plain film showed osteoblastic lesions of the right pelvic bone and lumbar spine. The pertinent routine laboratory findings revealed increased levels of serum alkaline phosphatase 125 U/L (normal 27-86). Metastatic prostate cancer was highly suspected and investigations focused upon this, including a serum prostate specific antigen assay, a transurethral cystoscopic examination, an intravenous pyelogram, and an ultrasonogram of the prostate gland. However, all of these investigations failed to support prostate cancer. Bone biopsy was performed twice, resulting in a report supporting Paget's disease of bone. The patient was treated with alendronate for three months. Radiologic findings, six months later, showed signs of improvement. He died one year later of heart failure that could plausibly had been a cardiovascular complication of Paget's disease. Better awareness of Paget's disease in Thailand and other Asian countries should reduce the incidence of unnecessary investigations and avoid a misleading diagnosis, which could lead to inappropriate treatment for metastatic prostatic cancer and undesirable psychological impact associated with being misinformed regarding malignancy.